Unveiling the risk period for death after respiratory syncytial virus Illness in young children using a self- controlled case series design - Li, Y; Campbell, H; Nair, H; Reeves, RM; Douglas, A; Meijer, A; Fischer, TK; Heikkinen, T; Giaquinto, C; Swanson, K; Stoszek, S; Leach, A; et al. (Oxford University Press, 2020)
Background: Respiratory syncytial virus (RSV)–related acute lower respiratory infection is an important cause of death in infants and young children. However, little is known about the risk period for RSV-related deaths after presentation to health services with an RSV illness.